Ambiguous Protection - Klaus Gründler; Arye L. Hillman (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Import regulations are globally the most prevalent form of intervention in international trade. The regulations should, under rules of the WTO, protect consumers and the environment but can be used to protect producers. We investigate the ambiguity of intent. We set out a model that when applied empirically suggests, as a benchmark estimate, equal divide between social benefit and producer protection. Inefficiency and distributional effects are consistent with producerprotecting trade policy. Country diversity in use of regulations supplements our estimates in suggesting producer-protecting intent. We look at how WTO procedures have allowed producer protection in the guise of social benefit.
Keywords: F13; F14; L15; L51; 330; protectionism; World Trade Organization; regulation; non-tariff barriers; public safety; environmental protection